TANTANGAN DAN PELUANG MSDM DALAM MENGHADAPI ERA DIGITALISASI DALAM INDUSTRI PERCETAKAAN ARIEZ - Sheva Prasetyo Budi Rahayu; Zaenal Anbiya; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Cross-border, 2023)
In the era of the digital revolution, human resources are an important factor in the success of a company. Companies that are able to turn challenges into opportunities can be more productive, innovative, and adaptive across generations. The purpose of this research is to find out the challenges and opportunities for human resource management at the Ariez printing company, Karawang and determine strategies for developing human resources for employees to increase productivity at the Ariez printing house. This article uses a descriptive method with observation. Data collection techniques are used as follows: observation, interview, documentation, and literature study. Data validity uses triangulation inspection techniques using sources. The results of this study are the challenges faced by Ariez Printing's human resource management in the digitalization era revolution, a lack of understanding of technological developments in the digital era. Current technological advances provide opportunities for Ariez printing to increase productivity such as increasing printing orders due to providing information and promotions to customers more quickly. In the era of digitalization, Ariez printing must make changes in policies and strategic programs for human resource development.